The Obsessive–Compulsive Symptoms in Tic Disorders and the Psychometric Properties of Children’s Yale–Brown Obsessive–Compulsive Scale: An Evidence-Based Survey in a Chinese Sample - Yan, Junjuan; Gu, Yi; Wang, Mengyu; Cui, Yonghua; Li, Ying (Frontiers in Pediatrics, 2022)
Objective: Patients with tic disorders (TDs) usually also have obsessive-compulsive disorder (OCD). The severity of obsessive-compulsive symptoms (OCS) in TD is widely evaluated using the Children’s Yale-Brown Obsessive-Compulsive Scale (CY-BOCS). However, there is no survey on the severity of OCS in TD patients based on a Chinese sample, and the reliability and validity of the CY-BOCS in patients with TD have not been well established in China. This study examined the severity of obsessive-compulsive symptoms in tic disorders and the psychometric properties of the CY-BOCS in Chinese pediatric patients with TD. Methods: A total of 367 patients diagnosed with TD (including 152 with Tourette syndrome) were enrolled from the Department of Psychiatry in Beijing Children’s Hospital in China. The mean age of the patients was 9.21 ± 2.06 years (range: 5–16 years). The Yale Global Tic Severity Scale (YGTSS) and CY-BOCS were used as screening tools. The psychometric properties of the CY-BOCS were assessed using Cronbach’s alpha, test-retest reliability, and construct validity. Results: The obsessive-compulsive symptoms in tic disorders were 3.93 ± 5.15 based on the CY-BOCS in the whole sample. The older adolescent group showed higher scores than the young adolescent groups (Z = -3.37, p = 0.001). However, the young adolescent group showed a higher incidence rate of OCS than the older adolescent group (p < 0.01). Males with TDs also showed a higher incidence rate of OCS than females (p = 0.03). The reliability and validity analyses of the CY-BOCS showed Cronbach’s alpha and test-retest reliability values of 0.81 and 0.82, respectively. The CY-BOCS showed an acceptable level in the two-factor structure (obsession and compulsive) in patients with TD. The comparative fit index was 0.84 for TD, 0.86 for Tourette, 0.94 for the younger adolescent group, and 0.74 for the older adolescent group. Conclusion: More obsessive-compulsive symptoms were identified in the Tourette syndrome group and the older adolescent group with tic disorders. The CY-BOCS showed good psychometric properties in children and adolescents with TD, especially in younger patients with TD. OCS might be associated with age and functional impairment of TD.